ANALISIS STABILITAS LOTION MENGGUNAKAN EMULSIFIER HASIL PENYABUNAN MINYAK DAN ALKALI - Armi Wulanawati; Chelsea Epriyani; Elline Sutanto (Jurnal Farmamedika (Pharmamedika Journal), 2019)
The lotion is one of the solid dispersion emulsion products with suitable emulsifiers. Lotion is included in cosmetics (personal care) which is usually used to moisturize, soften, and soften the skin. Types of emulsions in personal care are oil in water (o/w) emulsions which tend to be polar in nature. Emulsifiers that are often used in lotion making are emulsifiers that are formed using the saponification method of paraffin oil and triethanolamine alkali. The stability of this emulsion can be influenced by pH and viscosity (polarity) values. Emulsions that have a similar degree of polarity to oil, will tend to be stable. It is known, paraffin has a low polarity, while some other types of oils such as 2-Ethylhexyl Palmitate, Dicaprilyl Ether, Cocoglycerides, Octyldodecanol have a higher polarity, whereas some types of alkalis such as KOH flakes, AMP 95, AMP Ultra PC 3000, Tris Amino Ultra and Neutrol TE have a higher pH than Triethanolamine. Based on these things, the emulsifier in the lotion was formed by reacting stearic acid in various types of oils and alkalis which had higher polarity and pH values than the previous use of oils and alkalis. Mixing between the oil and alkaline phases is carried out at 70−75ºC to facilitate the emulsification process. The results obtained from the lotion emulsion stability test showed that the lotions in all types of oils and alkalis were stable at storage temperatures (room temperature, 45ºC, and 50ºC), and the pH was in the range of 6.75–7.60, but the best lotion emulsions and standards SNI 16-4399-1996 is using an emulsifier composed of Neutrol TE alkali and Octyldodecanol oil which has pH value 6.76-7.03, and viscosity 35000-43000 cP.